Developing a Policy Leadership Behaviours Scale: an Exploratory Factor Analysis - Noryati, Alias (AeU, 2015)
School administrators are challenged to lead, manage and control schools to ensure that they create the best conditions possible so that these schools may become educationally meaningful institutions for all. For this very reason, through existing “brilliantly written” policies surrounding schools, school leaders and administrators have to established the “policy leadership” in their positions as leaders and administrators in schools. The AN-Policy Leadership Behaviours Questionnaire VI (AN-PLBQ VI), was proposed as an instrument to measure policy leadership behaviours, was administered to 319 public school administrators in the state of Kuala Lumpur and Selangor, Malaysia. The original instrument had 89 items under 13 dimensions or factors identified as components that formulate policy leadership behaviours. The AN-PLBQ VI was subjected to exploratory factor analysis (EFA) using principal component analysis (PCA) with varimax rotation. The closing result of EFA suggested 61 items that are distributed on 10 original factors were specified to retain though items combined from different factors, that are: the ability to strategically plan for policy implementation, ability to frame and select policy issues, ability to actively participate in the policy process, ability to establish and work towards a set vision, ability to manage access to policy environment, ability to forge and nurture an accommodating policy culture, ability to manage public perception of policy, ability to conduct policy scanning, ability to conduct policy networking activities and ability to strategically plan for policy advantage. While another new and modified 3 factors from its original label were made to match the emerging new factors that are: ability to keep policy current, ability to keep policy aligned and ability to forge and nurture policy support. A confirmatory factor analysis is proposed to this new factor structure of AN-PLBQ VI in order for this exploration research moves to an explanation study.